Konrad Hirschler. The Written Word in the Medieval Arabic Lands: A Social and Cultural History of Reading Practices - Yayla, Mustafa Altuğ (Zemin, 2021)
Konrad Hirschler. The Written Word in the Medieval Arabic Lands: A Social and Cultural History of Reading Practices. Edinburgh: Edinburgh University Press, 2011. 304 s., ISBN 9780748642564.